Characterization of population aging in the state of Alagoas: Developments in social vulnerability (Research, Society and Development, 2021)
Objective: to describe how the aging population of the state of Alagoas is characterized, based on a bibliographic review research methodology on all articles found in relation to the aging of the elderly population in recent decades, using the Scientific Electronic Library Online databases (SciELO), PUBMED and data collected from the Brazilian Institute of Geography and Statistics - IBGE. Methodology: This is a descriptive study, with a cross-sectional design and quantitative approach, for data analysis obtained from the Demographic Censuses of the Brazilian Institute of Geography and Statistics (IBGE), released between the years 2000 to 2019. Results: Brazilian elderly they negatively assess their health condition and a fact corroborated in the indicators of health, illiteracy and gender and family relationships. Polypharmacy, musculoskeletal diseases and mental illnesses related to stress and depression are also pointed out as impacting factors in the low quality of health of the senile population in Alagoas. Conclusion: this article does not exhaust discussions and analyzes about the characterization of the elderly resident in the state of Alagoas, this population aging requires efficient indicators, health monitoring and strengthening of health care networks for the elderly, family and communities.